Oscillatory dynamics of a superconductor vortex lattice in high amplitude ac magnetic fields - Moreno, A. J. (2005)
We study by ac susceptibility measurements the evolution of the solid vortex lattice mobility under oscillating forces. It has already been shown that in YBCO single crystals, below the melting transition, a temporarily symmetric magnetic ac field (e.g., sinusoidal, square, triangular) can heal the vortex lattice (VL) and increase its mobility, but a temporarily asymmetric one (e.g., sawtooth) of the same amplitude can tear the lattice into a more pinned disordered state. In this work we present evidence that the mobility of the VL is reduced for large vortex displacements, in agreement with predictions of recent simulations. We show that with large symmetric oscillating fields both an initially ordered or an initially disordered VL configuration evolve towards a less mobile lattice, supporting the scenario of plastic flow. © 2005 The American Physical Society.